Solid Waste Management and Disposal Practice in Bauchi City, Nigeria - Kamaruddin, Siti Mazwin; Muhammed, Iliyasu (GEOGRAFI, 2022)
Municipal solid waste (MSW) services are critical elements of human societies and environmental infrastructure. In developing countries, household waste collection and disposal are the responsibility of local authorities, but often the volume of waste surpasses their collection capabilities. In addition, a lack of awareness and knowledge of sustainable waste practices contributes to poor waste practices. As a result, most waste ends in open dumps, roadsides, and other similar places. Massive waste disposal sites (locally termed Bingi) in every ward within the case study area, Bauchi old city are the most critical problem facing the Bauchi state environmental protection agency (BASEPA), responsible for solid waste collection and disposal. This study evaluates the disposal practices and constraints faced by residents, thus providing relevant information to BASEPA towards more effective implementation of sustainable waste management (SWM). Questionnaires were collected from 156 households, and the findings demonstrated a variety of households’ waste management practices and perceptions of BASEPA’s role and presence. In conclusion, the findings indicate that lack of awareness and ignorance of SWM practices still plague households, and insufficient waste facilities, finance, and lack of modernized waste equipment are probably the biggest constraints to solid waste disposal and management. These challenges bring several implications for the waste management authority’s role in plan implementation and regulatory enforcement. The study proposes several strategies to address and overcome these challenges.